2011
DOI: 10.1590/s1413-70542011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citric acid on the proteolytic activity of Zea mays L.

Abstract: MARTINEZ-PACHECO, M. M. et al. 908Ciênc. agrotec., Lavras, v. 35, n. 5, p. 908-915, set./out., 2011 Grain yield, soluble protein and proteolytic activity were monitored when the crop reached physiological maturity. Citric acid was applied before the appearance of the flag leaf, and induced an increase in the grain yield from 4222 to 5780 kg/ha, in the soluble protein from 6.34 to 7.91 mg/mg and into the proteolytic activity from 14.3 to 65.7 µU mg prot -1 . This is an increase of 2 to 12 times in the Falco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Citric acid was upregulated in the tolerant inoculated cultivars, but it was below the level of detection in the susceptible inoculated cultivars, proving its role in the defense of potato roots against Sss. Similarly, the role of citric acid in improving plant vigor against pathogen attack was also demonstrated in Zea mays [32]. Azelaic acid was also significantly upregulated in the tolerant cultivars in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…Citric acid was upregulated in the tolerant inoculated cultivars, but it was below the level of detection in the susceptible inoculated cultivars, proving its role in the defense of potato roots against Sss. Similarly, the role of citric acid in improving plant vigor against pathogen attack was also demonstrated in Zea mays [32]. Azelaic acid was also significantly upregulated in the tolerant cultivars in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…Also, Ström et al (2005) report that the nutrient extraction efficiency increases through the application of citric acid (10 mM). Martinez-Pacheco et al (2011) reported that citric acid differentially induced proteolytic activity and vigor in the corn hybrids. Sadak et al (2013) reported that coapplication of ascorbic acid and citric acid may alleviate the harmful effects of salinity stress.…”
Section: Introductionmentioning
confidence: 99%